Investment Assessments in the Adoption of Accessible and Assistive Technologies Within Built Environments for Persons with Disabilities - Siny Joseph; Vinod Namboodiri (Buildings)
Emerging trends in technology are providing opportunities for a broader range of accessible and assistive technologies (AATs) to positively impact persons with disabilities in terms of independent living and employment within and across built environments. However, such technologies typically require significant investments by entities that offer such options. It is not clear how such firms compete in a market with other firms that may not provide such options. Understanding such competition can help to promote greater investments in accessibility infrastructure within built environments by entities and provide insights into how federal efforts can further boost such efforts. To this end, this paper presents a game-theoretic framework of market competition between two firms where one invests in accessibility (bearing additional upfront costs) and compares it with another one that does not. Numerical evaluations demonstrate the range of parametric values where accessibility investments pay off. Furthermore, case studies are presented to demonstrate the practical feasibility of these parameter values. The results indicate that any firm considering making accessibility investments can expect to make profits and also gain an advantage over its competitors if the expected increase in the average user experience is significant (quantified as 20% or more for the parameters considered in this work) across all potential users.